Workshop Media Pembelajaran Dalam Melatih Guru Menciptakan Pengalaman Belajar Yang Interaktif Dan Menarik di SMP Negeri 2 Batukliang - Haerul Johdi; Baiq Andriani Saputri; Baiq Maulida Titin Fatimah; Fathoni Arif Pratama; Nila Vidia Ekayanti (Indonesian Journal of Education and Community Services, 2024)
Mastery of effective learning media is a crucial skill for teachers to create interactive and engaging learning experiences. This activity is part of the Kampus Mengajar program, aimed at enhancing teachers' understanding of the functions, uses, and potential of various modern learning media. Through this workshop, teachers were encouraged to explore creative ideas in utilizing modern learning media to improve the appeal and interactivity of the learning process. The methods used included practical training and interactive discussions that delved into the integration of learning media. The workshop results showed an increase in teachers' understanding of using learning media to support more engaging and enjoyable teaching processes. This activity is expected to motivate teachers to implement learning media in their daily teaching activities, thereby fostering a more meaningful learning atmosphere for students.